LAS ACTITUDES HACIA LOS INMIGRANTES EN MÉXICO: EXPLICACIONES ECONÓMICAS Y SOCIALES - Meseguer, Covadonga; Maldonado, Gerardo (El Colegio de México A.C., 2015)
The attitudes of Mexicans towards migrants may be explained by the fear of encountering competition in the labor market, as well as by social concerns such as ethnicity or threats to security. To explore these hypotheses, we use data from the project Mexico, the Americas and the World. Our results are in line with the attitudes towards immigrants in advanced countries. Social disposition, rather than economic concerns, better explain attitudes towards immigrants in general and towards both groups of foreigners in particular. Specifically, we find that concerns about security and a moderate level of ethnocentrism determine attitudes and opinions of Mexicans towards immigrants.